Pelatihan dan Implementasi Sistem Informasi Geografis (SIG) dalam Pemetaan Jalan Rusak di Desa Ridan Permai - Adeswastoto, Hanantatur; Febryanto; Islami, Fajril (Journal of Social and Community Service, 2022)
This program maps road damage using GIS in Ridan Permai Village to support village infrastructure development policy making based on geospatial data. This activity is carried out as a form of community service with the aim of providing visual information and accurate and up-to-date road damage condition data. The methods used are field surveys, collecting geometric road data, and data processing using ArcGIS software. The analysis was carried out using the PCI (Pavement Condition Index) approach to classify the level of damage based on the type of pavement. The mapping results show that most of the roads in Ridan Permai Village are in poor to very poor condition, especially on the village entrance and exit routes. This information is very important for the village government in determining the priority scale of repairs, preparing budget plans, and optimizing the use of village funds. This program also encourages increased public understanding of the importance of infrastructure maintenance based on spatial data.